Danizg - Buchholz, Max (1878-po 1942). (Danzig : [s.n., 1930)
Folder reklamowy Gdańska.
Keywords: Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- wydawnictwa ilustrowane; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto).